Thoughts on Developmental and Psychoanalytic Change Inspired by Heinz Hartmann. Issue 3 (3rd April 2022) - Harrison, Alexandra M.; Tronick, Ed
ABSTRACT: Rather than attempting to review Hartmann's extensive contributions to psychoanalytic theory, we are going to follow his example by suggesting a biological meta-theory for psychoanalysis, focusing in particular on adaptation, and also addressing "reality." We introduce a nonlinear model that highlights the dyad as the common pathway for developmental change – such as the infant-caregiver dyad in early development and the patient-analyst dyad in psychoanalysis. Then we offer a clinical illustration from a child analytic case. We will close with some observations about "adaptation to reality" in remote child therapy during COVID.